Covalent immobilization of acetylcholinesterase on a novel polyacrylic acid-based nanofiber membrane - OGAN, AYŞE; KAHRAMAN, MEMET VEZİR; DEMİR, SERAP (WILEY, 2018)
In this study, polyacrylic acid-based nanofiber (NF) membrane was prepared via electrospinning method. Acetylcholinesterase (AChE) from Electrophorus electricus was covalently immobilized onto polyacrylic acid-based NF membrane by demonstrating efficient enzyme immobilization, and immobilization capacity of polymer membranes was found to be 0.4 mg/g. The novel NF membrane was synthesized via thermally activated surface reconstruction, and activation with carbonyldiimidazole upon electrospinning. The morphology of the polyacrylic acid-based membrane was investigated by scanning electron microscopy, Fourier Transform Infrared Spectroscopy, and thermogravimetric analysis. The effect of temperature and pH on enzyme activity was investigated and maxima activities for free and immobilized enzyme were observed at 30 and 35 degrees C, and pH 7.4 and 8.0, respectively. The effect of 1 mM Mn2+, Ni2+, Cu2+, Zn2+, Mg2+, Ca2+ ions on the stability of the immobilized AChE was also investigated. According to the Michaelis-Menten plot, AChE possessed a lower affinity to acetylthiocholine iodide after immobilization, and the Michaelis-Menten constant of immobilized and free AChE were found to be 0.5008 and 0.4733 mM, respectively. The immobilized AChE demonstrated satisfactory reusability, and even after 10 consecutive activity assay runs, AChE maintained ca. 87% of its initial activity. Free enzyme lost its activity completely within 60 days, while the immobilized enzyme retained approximately 70% of the initial activity under the same storage time. The favorable reusability of immobilized AChE enables the support to be employable to develop the AChE-based biosensors.
Keywords: Acetylcholinesterase; Covalent immobilization; Electrospinning; NF membrane; Polyacrylic acid; BIOMEDICAL APPLICATIONS; MAGNETIC NANOPARTICLES; POLY(ACRYLIC ACID); GLUCOSE-OXIDASE; HYDROXYAPATITE; PERFORMANCE; STABILITY; ELECTRODE; SURFACE